Correlates and moderators of physical activity in parent-tween dyads: a socio-ecological perspective. Issue 9 (September 2015) - Bélanger-Gravel, A.; Gauvin, L.; Lagarde, F.; Laferté, M.
Abstract Objectives The identification of correlates and moderators of physical activity (PA) among parents and their children can support the development of more effective interventions. The aims of this study were to identify individual- and family-level predictors of PA among parent-tween dyads and to examine the moderating role of socio-economic status (SES) on these associations. Study design As part of a larger investigation, a cross-sectional telephone survey was conducted in 2012 among 1000 parent-child dyads. Methods Children were aged between nine and 13 years (tweens). Frequency of participation in PA was self-reported by means of questionnaires. Multilevel modelling was used. Individual predictors included body mass index and sedentary lifestyles whereas family-level predictors included parents' cognitions, family co-participation in PA, and socio-economic characteristics. Results Significant between-dyad variability in PA was observed among parent-daughter dyads (n = 470, ICC = 0.17, P < 0.001) but not parent-son dyads (n = 520, ICC = 0.01, P = 0.37). Sedentary activity (ps < 0.001) and co-participation in PA (ps < 0.001) were associated with greater PA. Positive parental perceptions of facilitating factors and greater self-efficacy were associated with PA among parent-daughter dyads (ps < 0.04) while parents' outcomes expectancies were associated with PA among parent-son dyads (P = 0.04). The relationship between facilitating factors and PA was moderated by SES (education) among parent-daughter dyads (P = 0.009). Conclusions Promoting co-participation in PA and less sedentary activities appear as useful targets for increasing PA among parents and tweens. Additional strategies might be considered according to the sex of the children and family SES. Future research addressing socio-economic inequalities in the correlates of PA among families with tween girls is required.